RIS-Assisted MIMO Channel Measurements and Characteristics Analysis for 6G Wireless Communication Systems - Sun, Yingzhuo; Wang, Cheng Xiang; Xu, Yingjie ; 0000-0003-2462-2317; Xin, Lijian; Huang, Jialing; Huang, Jie; Qin, Qibo; Gao, Xinyu; Guo, Bolun; Cui, Tie Jun; Chen, Yunfei (IEEE Transactions on Vehicular Technology, 2025)
Reconfigurable intelligent surface (RIS) can manipulate the electromagnetic (EM) waves in wireless channels and thus is promising for the sixth generation wireless communication systems. However, there exists little research on RIS channel measurements, which are important for the communication system design. In this paper, channel measurements are carried out in anechoic chamber, outdoor, and indoor environments. For anechoic chamber measurements, the insertion loss, EM response reciprocity, and received power are analyzed. It is found that RIS can fulfill EM response reciprocity. It is also found that the performance of RIS beamforming in the coplane configuration is better than that in the non-coplane configuration. In outdoor measurements, the cumulative distribution functions of large-scale parameters (LSPs) are obtained to explore the relationship between LSPs and heights. Results show that the RIS-user equipment channel is more sensitive to the height variation than the base station-RIS channel. For indoor measurements, the angular power spectral density, spatial cross-correlation function, and channel capacity are investigated. It is found that RIS with near-field coding and a larger size can bring a higher gain than RIS with far-field coding and a smaller size. The normalized power and code differences between near-field and far-field coding are defined to verify the RIS Rayleigh distance. It can be found that the value of the theoretical RIS Rayleigh distance is almost the same as the distance where the defined normalized differences become zero.
Keywords: 6G wireless communication systems; channel characteristics; channel measurements; reconfigurable intelligent surface (RIS)